2010
DOI: 10.1080/10590501.2010.504979
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Genotoxicity of Avocado (Persea americana) Fruit and Leaf Extracts in Human Peripheral Lymphocytes

Abstract: Persea americana is much sought after both for the nutritional value of its fruit and the medicinal values of its various plant parts. A chromosomal aberration assay was undertaken to evaluate the potential genotoxicity of crude extracts from avocado fruits and leaves. Chromosomal aberrations were observed in cultured human peripheral lymphocytes exposed to separately increasing concentrations of 50% methanolic extracts of Persea americana fruit and leaves. The groups exposed to leaf and fruit extracts, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Therefore, it is considered that the P. americana seed extract showed no genotoxic activity with the micronucleus test. There is a study that demonstrates the genotoxicity of the avocado fruit and leaf extracts in human peripheral lymphocytes [ 14 ]; however, this study was carried out in vitro . There are different toxic effects in vitro and in vivo , especially when it is administered orally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is considered that the P. americana seed extract showed no genotoxic activity with the micronucleus test. There is a study that demonstrates the genotoxicity of the avocado fruit and leaf extracts in human peripheral lymphocytes [ 14 ]; however, this study was carried out in vitro . There are different toxic effects in vitro and in vivo , especially when it is administered orally.…”
Section: Discussionmentioning
confidence: 99%
“…Avocado leaves showed cardiotoxic effects in mammals and birds [ 10 – 13 ]. Similarly, the mutagenicity of fruit and leaves extracts in human lymphocytes has been assessed [ 14 ]. However, no study has been done to examine the possible genotoxic activity of avocado seed extract.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, contradicting information regarding avocado extract-induced genotoxicity is also available. For instance, Kulkarn et al [157] found out that avocado fruit and leaf extracts can induce chromosomal aberrations in human peripheral lymphocytes, with leaf extract being more genotoxic. The same research group later reported that avocado fruit extract can reduce cyclophosphamide-mediated chromosomal aberrations in human lymphocytes [158], which was perhaps due to the antagonistic effects of the extract on cyclophosphamide.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, plants such as Viscum album, Asparagus racemos, Panax ginseng and Tinospora cordifolia are known to have strong effects on immune responses [40]. Studies by Kulkarni et al in 2010 also revealed that the Avocado fruit has strong beneficial effects on immune responses, together with some minor cytotoxic effects [41]. Boosting the immune system with extracts from medicinal plants will enhance its capacity to respond to chemotherapy and radiotherapy-induced killing of cancer cells by promptly mopping up such dying or dead cancer cells, expressing the features of apoptosis.…”
Section: Medicinal Plants and Anti-cancer Immune Responsesmentioning
confidence: 99%